Ästhetik des Depressiven - Huber, Till; Nover, Immanuel (spectrum Literaturwissenschaft / spectrum Literature, 2023)
Medical, sociological, and journalistic discourse currently views depression as the dominant psychological disease in modern societies. This volume examines narrative texts of the early twentieth century and contemporary literature from a literary studies perspective to investigate the motifs and literary devices of the depressive, depressive characters, and relevant stagings by authors.